RATIONALIZED MACROSTRUCTURE OF WOOD PARTICLE BASED COMPOSITES (Innovation in Woodworking Industry and Engineering design, 2026)
Subject of the study is the macrostructure of wood particle based composites (WPBC) and the possible rationalization of their significant structural parameters with the goal of increasing the effectiveness of material’s use in the design practice.The physical nature of the WPBC can be defined as an anisotropic layered wood-polymeric material, fabricated from adhesively bonded wood particles. The macrostructure characteristics and the physical and mechanical properties of the composite material predeter-mine it’s broad application in the furniture production.The rationalized macro structural characteristic of the WPBC is established on the basis of theoretical and experimental studies determining the effective dimensions and dispersion of the wood particles. Structural deformation and strength models are developed and analyzed for short and long-term loading.The impact of the major structural parameters on the complex qualitative indicator of WPBC is defined using mathematical regression modeling.